1982
DOI: 10.1002/chin.198243156
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: ALKENE‐ALKANE ALKYLATION CATALYZED BY THE HYDROGEN FLUORIDE‐TANTALUM PENTAFLUORIDE ACID SYSTEM

Abstract: Die Alkylierung der niedrigkettigen Alkane (III) mit dem aus Ethylen (I)/HF‐TaF5 intermediär erzeugten Ethylkation (II) zu den Ethylalkanen (IV) wird untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Anyhow, one may expect, that the nature of the insertion reaction is similar to that of its backward analogs like the primary demethanation of light alkanes coupled with the formation of lower olefins which was observed in many studies (see, e.g., [1,[35][36][37][38]). Indeed, this demethanation via Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Anyhow, one may expect, that the nature of the insertion reaction is similar to that of its backward analogs like the primary demethanation of light alkanes coupled with the formation of lower olefins which was observed in many studies (see, e.g., [1,[35][36][37][38]). Indeed, this demethanation via Fig.…”
Section: Discussionmentioning
confidence: 93%
“…If the ethyl cation had reacted with excess ethylene, primary 1-butyl cation would have been formed which irreversibly would rearrange to the more stable .sec-butyl cation and subsequently to the rm-butyl cation giving isobutane as the end product. Despite unfavorable experimental conditions in a batch system for kinetically controlled reactions, Sommer et al have found (36) that selectivity of 80% in nbutane was achieved through the ethylation of ethane. The results indicate that to succeed in the direct alkylation the following conditions have to be met.…”
Section: C-ch 3 -• Oligomersmentioning
confidence: 97%
“…This can be achieved in the condensation process of oxidative nature, where hydrogen is removed by the oxidant (34). Alkylation of methane , ethane, propane and η-butane by the ethyl cation obtained by the protonation of ethylene in superacid media has been investigated by Siskin, (35) Sommer et al (36) and Olah and coworkers (37), respectively. The difficulty lies in generating in a controlled way a very energetic primary carbocation in the presence of alkane and at the same time avoiding oligocondensation of the ethylene itself.…”
Section: C-ch 3 -• Oligomersmentioning
confidence: 99%
“…Alkylation of methane, ethane, propane, and n-butane by the ethyl cation generated via protonation of ethylene in superacid media has been studied by Siskin, 148 Sommer et al, 149 and Olah et al 150 The difficulty lies in generating in a controlled way a very energetic primary carbenium ion in the presence of excess methane and at the same time avoiding oligocondensation of ethylene itself. Siskin Propane as a degradation product of polyethylene (a byproduct in the reaction) was ruled out because ethylene alone under the same conditions does not give any propane.…”
Section: Alkylation Of Alkanes and Oligocondensation Of Lower Alkanesmentioning
confidence: 99%
“…The yield of the alkane-alkene alkylation in homogeneous HF-TaF 5 depending on the alkene-alkane ratio has been investigated by Sommer et al 149 in a batch system with short reaction times. The results support direct alkylation of methane, ethane, and propane by the ethyl cation and the product distribution depends on the alkene-alkane ratio ( Figure 5.14).…”
Section: ð5:66þmentioning
confidence: 99%